Genetic variation of Borreliella burgdorferi in Fairfax County, Virginia, targeting the OspC gene in white-footed mice - Zawada, Sonya G.; von Fricken, Michael E.; Weppelmann, Thomas A.; Sikaroodi, Masoumeh; Gillevet, Patrick M. (Frontiers in Microbiology, 2022)
Outer surface protein C (OspC) is a commonly used marker in population studies of Borreliella to differentiate types and establish evolution over time. Investigating the ospC genetic types of Borreliella burgdorferi across multiple organ tissues of white-footed mice has the potential to contribute to our understanding of Lyme disease and the wide spectrum of clinical presentation associated with infection. In this study, five unique tissue types were sampled from 90 mice and screened for B. burgdorferi infections. This initial screening revealed a 63% overall B. burgdorferi infection rate in the mice collected (57/90). A total of 163 tissues (30.4%) tested positive for B. burgdorferi infections and when mapped to Borreliella types, 143,894 of the initial 322,480 reads mapped to 10 of the reference sequences in the ospC strain library constructed for this study at a 97% MOI. Two tissue types, the ear and the tongue, each accounted for 90% of the observed Borreliella sequence diversity in the tissue samples surveyed. The largest amount of variation was observed in an individual ear tissue sample with six ospC sequence types, which is equivalent to 60% of the observed variation seen across all tested specimens, with statistically significant associations observed between tissue type and detected Borreliella. There is strong evidence for genetic variability in B. burgdorferi within local white-footed mouse populations and even within individual hosts by tissue type. These findings may shed light on drivers of infection sequalae in specific tissues in humans and highlights the need for expanded surveillance on the epigenetics of B. burgdorferi across reservoirs, ticks, and infected patients.